Social epistemic actions. (28th May 2020) - Pezzulo, Giovanni; Barca, Laura; Maisto, Domenico; Donnarumma, Francesco
Abstract: We consider the ways humans engage in social epistemic actions, to guide each other's attention, prediction, and learning processes towards salient information, at the timescale of online social interaction and joint action. This parallels the active guidance of other's attention, prediction, and learning processes at the longer timescale of niche construction and cultural practices, as discussed in the target article.